Mending a broken heart by biomimetic 3D printed natural biomaterial-based cardiac patches: a review - Rosellini, Elisabetta; Cascone, Maria Grazia; Guidi, Lorenzo; Schubert, Dirk W.; Roether, Judith A.; Boccaccini, Aldo R. (Frontiers in Bioengineering and Biotechnology, 2023)
Myocardial infarction is one of the major causes of mortality as well as morbidity around the world. Currently available treatment options face a number of drawbacks, hence cardiac tissue engineering, which aims to bioengineer functional cardiac tissue, for application in tissue repair, patient specific drug screening and disease modeling, is being explored as a viable alternative. To achieve this, an appropriate combination of cells, biomimetic scaffolds mimicking the structure and function of the native tissue, and signals, is necessary. Among scaffold fabrication techniques, three-dimensional printing, which is an additive manufacturing technique that enables to translate computer-aided designs into 3D objects, has emerged as a promising technique to develop cardiac patches with a highly defined architecture. As a further step toward the replication of complex tissues, such as cardiac tissue, more recently 3D bioprinting has emerged as a cutting-edge technology to print not only biomaterials, but also multiple cell types simultaneously. In terms of bioinks, biomaterials isolated from natural sources are advantageous, as they can provide exceptional biocompatibility and bioactivity, thus promoting desired cell responses. An ideal biomimetic cardiac patch should incorporate additional functional properties, which can be achieved by means of appropriate functionalization strategies. These are essential to replicate the native tissue, such as the release of biochemical signals, immunomodulatory properties, conductivity, enhanced vascularization and shape memory effects. The aim of the review is to present an overview of the current state of the art regarding the development of biomimetic 3D printed natural biomaterial-based cardiac patches, describing the 3D printing fabrication methods, the natural-biomaterial based bioinks, the functionalization strategies, as well as the in vitro and in vivo applications.